1998
DOI: 10.4319/lo.1998.43.3.0471
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of dissolved methane in a eutrophic, shallow lake: Lake Kasumigaura, Japan

Abstract: Long-term seasonal variations in water-column methane oxidation were studied in the eutrophic, shallow Lake Kasumigaura, Japan. The entire water column was oxic throughout the year. Measurements were taken monthly from July 1991 to March 1996. The oxidation rates were derived from time-course dissolved methane concentration measurements during the bottle incubation at in situ temperature. The existence of methane oxidation activity in the oxic lake water was confirmed. Methane oxidation was distinctly seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 24 publications
8
47
1
1
Order By: Relevance
“…In accord with previous reports (Utsumi et al 1998;Whiticar 1999;Karim et al 2011;Harley et al 2015), the oxidation of CH 4 is enhanced by higher water temperatures. This conclusion is supported by the decrease in C HC in warmer seasons (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…In accord with previous reports (Utsumi et al 1998;Whiticar 1999;Karim et al 2011;Harley et al 2015), the oxidation of CH 4 is enhanced by higher water temperatures. This conclusion is supported by the decrease in C HC in warmer seasons (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…However, in the present study, the sampled lakes were in many cases shallow, relatively well mixed, and without a clear oxycline (see Results section), suggesting a relatively homogeneous water column. Utsumi et al (1998b) observed homogeneous MO rates at all depths of a shallow and mixed temperate lake, while Rudd and Hamilton (1978) also reported homogeneous MO rates during overturn of a dimictic lake. Determination of MO rates at the oxic/anoxic interface, in the few cases in which such an interface was observed, would likely have indicated higher MO rates.…”
Section: Limiting Factors Of Mo Ratesmentioning
confidence: 94%
“…This rate is higher than previous estimates from in vitro incubations for oligotrophic Lake Stechlin, Germany (0.04-0.09 mmol m À 3 per day) 18,19 , but it should be noted that this estimate is very sensitive to the values of MOX used. In-situ MOX can vary dramatically across systems 31 , with depth, diurnally and with changes in light exposure 18,19 . Therefore, it is possible that our estimates of MOX and methanogenesis may be biased by the fact that water from only one depth was used, and incubations were run in the dark (see Methods section for details).…”
Section: Discussionmentioning
confidence: 99%
“…4). This approach was deemed more accurate in quantifying the slope at time 0, as traditional methods, such as log transformations followed by visual selection of the linear portion of the data set 31 , can introduce large errors in the slope of the regression line when deciding which points to fit and which to exclude. Although MOX was estimated only once, our estimates are within the range of pelagic MOX (0.170-0.250 mmol m À 3 per day) previously reported 31,32,62 , particularly for boreal lakes of similar trophic condition 62 .…”
Section: Methodsmentioning
confidence: 99%